2021
DOI: 10.1111/1745-5871.12460
|View full text |Cite
|
Sign up to set email alerts
|

Changing geographies of fashion during COVID‐19: The Australian case

Abstract: COVID‐19 has impacted a range of industries, of which the fashion industry is no exception. Here, we examine the effects of COVID‐19 on the geographies of that industry in Australia. We use a path‐dependency framework to understand the evolution of the Australian fashion industry and to evaluate the impact of COVID‐19 as an external shock to this evolution. The Australian fashion industry has been hit particularly hard by the pandemic. Drawing upon a qualitative methodology and associated set of methods consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Moreover, only 34% of companies reported that they were confident in their ability to rebound post-COVID [61]. Australian fashion brands reported experiencing supply chain disruptions, including delays from fabric suppliers, closures of off-shore production facilities, increased freight costs, and canceled orders, as well as impacts to retail, such as closing retail stores to comply with government lockdowns, excess unsold stock, and shifting consumer sentiments, which functioned as a catalyst for brands to reassess their business models [62]. Fashion brands with existing commitments to social purposes and sustainable manufacturing methods, such as made-to-order models, in-house manufacturing, and garment re-purposing, were least impacted by COVID-19 [63,64].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only 34% of companies reported that they were confident in their ability to rebound post-COVID [61]. Australian fashion brands reported experiencing supply chain disruptions, including delays from fabric suppliers, closures of off-shore production facilities, increased freight costs, and canceled orders, as well as impacts to retail, such as closing retail stores to comply with government lockdowns, excess unsold stock, and shifting consumer sentiments, which functioned as a catalyst for brands to reassess their business models [62]. Fashion brands with existing commitments to social purposes and sustainable manufacturing methods, such as made-to-order models, in-house manufacturing, and garment re-purposing, were least impacted by COVID-19 [63,64].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social media also functioned as an important tool for continued retail and marketing activities. In particular, Instagram enabled fashion brands to sell, promote, and connect with their consumers following the emergence of COVID-19 [62]. Consequently, COVID-19 facilitated the development of "post-covid" strategies by Australian fashion brands, which included the amplification of digital sales and marketing, a renewed investment in the Australian supply chain, and embracing more sustainable practices, such as incorporating a circular economy and waste recycling principles [61].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, in order to stay resilient, the COVID-19 pandemic has forced the Muslim fashion industry to be adaptive, collaborative, innovative, and creative in order to develop new products based on types of consumer feedback such as OPRs [6], as well as to improve service and product quality [28]. These changes require the fashion industry to be more innovative and adaptable in order to reduce the spread of COVID-19 [29].…”
Section: Oprs Are Used To Support the Resilience Of Muslim Fashion In...mentioning
confidence: 99%
“…This raises people's expectations for sustainable clothing production that has a specific purpose. [21] In facing the challenges of the Covid-19 pandemic, there are three important keys so that creative economy actors in the fashion sector can continue to survive, and even become winners. The three keys are digitization, innovation, and adaptation.…”
Section: Fashion Sub-sectormentioning
confidence: 99%